Biocontrol potential of native isolates of Beauveria bassiana against cotton leafworm Spodoptera litura (Fabricius) - Shah Mohammad Naimul Islam; Md. Zahid Hasan Chowdhury; Mahjabin Ferdaous Mim; Milia Bente Momtaz; Tofazzal Islam (Scientific Reports, 2023)
Abstract The entomopathogenic fungus (EPF), Beauveria bassiana, is reported as the most potent biological control agent against a wide range of insect families. This study aimed to isolate and characterize the native B. bassiana from various soil habitats in Bangladesh and to evaluate the bio-efficacy of these isolates against an important vegetable insect pest, Spodoptera litura. Seven isolates from Bangladeshi soils were characterized as B. bassiana using genomic analysis. Among the isolates, TGS2.3 showed the highest mortality rate (82%) against the 2nd instar larvae of S. litura at 7 days after treatment (DAT). This isolate was further bioassayed against different stages of S. litura and found that TGS2.3 induced 81, 57, 94, 84, 75, 65, and 57% overall mortality at egg, neonatal 1st, 2nd, 3rd, 4th, and 5th instar larvae, respectively, over 7 DAT. Interestingly, treatment with B. bassiana isolate TGS2.3 resulted in pupal and adult deformities as well as decreased adult emergence of S. litura. Taken together, our results suggest that a native isolate of B. bassiana TGS2.3 is a potential biocontrol agent against the destructive insect pest S. litura. However, further studies are needed to evaluate the bio-efficacy of this promising native isolate in planta and field conditions.